Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Pollen transport to deep-marine environments: Considerations for reconstructing past vegetation from marine sediment cores - Laura S. McDonald; Lorna J. Strachan; Katherine Holt; Adam D. McArthur; Anthony E. Shorrock; Martin P. Crundwell; Katharina Pank; Madison Clarke; Adam Woodhouse; Davide Gamboa; Jenni L. Hopkins; Matt S. McGlone; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Integrated onshore–offshore paleoseismic records show multiple slip styles on the plate interface, central Hikurangi subduction margin, Aotearoa New Zealand - Charlotte O. Pizer; Jamie D. Howarth; Kate J. Clark; Alan R. Orpin; Stephanie E. Tickle; Lorna J. Strachan; Philip Barnes; Sian Camp; Monique Mckeown; Emily Twort (Quaternary Science Reviews, 2024)

Using pollen in turbidites for vegetation reconstructions - Laura S. McDonald; Lorna J. Strachan; Katherine Holt; Adam D. McArthur; Philip M. Barnes; Katherine L. Maier; Alan R. Orpin; Mark Horrocks; Aratrika Ganguly; Jenni L. Hopkins; Helen C. Bostock (Journal of Quaternary Science, 2024)
Turbidites, deposited by sub‐aqueous gravity flows, are common in sedimentary archives worldwide and present a unique challenge and opportunity when reconstructing past vegetation through pollen analysis. When sampling pollen from a sediment core for palaeovegetation records, it is common practice to target background sediments (i.e. pelagic sediment) and avoid sampling turbidites, as they are presumed to portray a misleading picture of past vegetation. This assumption stems from our limited understanding of pollen abundance and distribution through turbidites, meaning that palynologists overlook deposits that could potentially be used to reconstruct past vegetation and climate. We present pollen assemblage and sedimentological data from four recent (

Overprinting orogenic events, ductile extrusion and strain partitioning during Caledonian transpression, NW Mainland Shetland - Timothy B. Armitage; Robert E. Holdsworth; Robin A. Strachan; Edward D. Dempsey; Richard J. Walker; Diana T. Alvarez-Ruiz; Geoffrey E. Lloyd (Journal of Structural Geology, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Erratum to: Impacts of boreal hydroelectric reservoirs on seasonal climate and precipitation recycling as simulated by the CRCM5: a case study of the La Grande River watershed, Canada - C. Irambona; B. Music; D. F. Nadeau; T. F. Mahdi; I. B. Strachan (Theoretical and Applied Climatology, 2018)

Impacts of boreal hydroelectric reservoirs on seasonal climate and precipitation recycling as simulated by the CRCM5: a case study of the La Grande River watershed, Canada - C. Irambona; B. Music; D. F. Nadeau; T. F. Mahdi; I. B. Strachan (Theoretical and Applied Climatology, 2018)

Environmental controls on the distribution of salt‐marsh foraminifera from the southern coastline of South Africa - Kate L. Strachan; Jemma M. Finch; Trevor R. Hill; Robert L. Barnett; Craig D. Morris; Peter Frenzel (Journal of Biogeography, 2016)
Aim Salt‐marsh foraminifera are widely used as robust sea‐level indicators. High‐resolution Holocene sea‐level reconstructions depend on the accurate characterization of modern foraminifera‐environment relationships representative of a study site. We investigate the relationship between modern foraminiferal assemblage distribution and key environmental variables, viz . elevation above land levelling datum ( LLD ), sediment grain size, organic content, pH and salinity. We hypothesize that the distribution of modern salt‐marsh foraminifera is primarily controlled by elevation above LLD . Location Knysna and Keiskamma estuaries along the southern coastline of South Africa. Methods Salt‐marsh surface sediment samples ( n = 97) were collected along eight intertidal transects with corresponding environmental data ( pH , salinity, organic content, sand, silt, clay and elevation). Multivariate ordination analysis (partial redundancy analysis; pRDA ) was used to investigate the relationship between living foraminiferal assemblages and environmental controls, after accounting for spatial variability in community composition. Results The pRDA suggests that species composition varied spatially within estuaries, but was strongly influenced by elevation at Keiskamma ( r = 0.63) and Knysna ( r = −0.75). At Keiskamma, the main gradient in composition was also influenced by salinity ( r = −0.63), in an equal and opposite manner to elevation. Composition at Keiskamma was influenced to a much lesser extent by sediment organic content ( r = 0.20) and the clay fraction ( r = −0.13). At Knysna, pH ( r = 0.455) was a secondary determinant of composition, and sediment characteristics covaried with elevation. Main conclusion Elevation was found to be a key environmental variable controlling the distribution of salt‐marsh foraminifera at both estuaries, thereby validating the use of foraminifera as sea‐level indicators. Certain species were particularly sensitive to elevation changes and could thus serve as useful indicators of past sea‐level change. This is an important first step towards the development of high‐resolution sea‐level reconstructions for the South African coastline.

Gene co-expression analysis identifies brain regions and cell types involved in migraine pathophysiology: a GWAS-based study using the Allen Human Brain Atlas - Else Eising; Sjoerd M. H. Huisman; Ahmed Mahfouz; Lisanne S. Vijfhuizen; Verneri Anttila; Bendik S. Winsvold; Tobias Kurth; M. Arfan Ikram; Tobias Freilinger; Jaakko Kaprio; Dorret I. Boomsma; Cornelia M. van Duijn; et al. (Human Genetics, 2016)

Rare taxa have potential to make metabolic contributions in enhanced biological phosphorus removal ecosystems - Christopher E. Lawson; Blake J. Strachan; Niels W. Hanson; Aria S. Hahn; Eric R. Hall; Barry Rabinowitz; Donald S. Mavinic; William D. Ramey; Steven J. Hallam (Environmental Microbiology, 2015)
Summary Enhanced biological phosphorus removal ( EBPR ) relies on diverse but specialized microbial communities to mediate the cycling and ultimate removal of phosphorus from municipal wastewaters. However, little is known about microbial activity and dynamics in relation to process fluctuations in EBPR ecosystems. Here, we monitored temporal changes in microbial community structure and potential activity across each bioreactor zone in a pilot‐scale EBPR treatment plant by examining the ratio of small subunit ribosomal RNA ( SSU r RNA ) to SSU r RNA gene (r DNA ) over a 120 day study period. Although the majority of operational taxonomic units ( OTUs ) in the EBPR ecosystem were rare, many maintained high potential activities based on SSU r RNA : r DNA ratios, suggesting that rare OTUs contribute substantially to protein synthesis potential in EBPR ecosystems. Few significant differences in OTU abundance and activity were observed between bioreactor redox zones, although differences in temporal activity were observed among phylogenetically cohesive OTUs . Moreover, observed temporal activity patterns could not be explained by measured process parameters, suggesting that other ecological drivers, such as grazing or viral lysis, modulated community interactions. Taken together, these results point towards complex interactions selected for within the EBPR ecosystem and highlight a previously unrecognized functional potential among low abundance microorganisms in engineered ecosystems.

Cryptic ecology among host generalist Campylobacter jejuni in domestic animals - Samuel K. Sheppard; Lu Cheng; Guillaume Méric; Caroline P. A. de Haan; Ann‐Katrin Llarena; Pekka Marttinen; Ana Vidal; Anne Ridley; Felicity Clifton‐Hadley; Thomas R. Connor; Norval J. C. Strachan; Ken Forbes; et al. (Molecular Ecology, 2014)
Homologous recombination between bacterial strains is theoretically capable of preventing the separation of daughter clusters, and producing cohesive clouds of genotypes in sequence space. However, numerous barriers to recombination are known. Barriers may be essential such as adaptive incompatibility, or ecological, which is associated with the opportunities for recombination in the natural habitat. Campylobacter jejuni is a gut colonizer of numerous animal species and a major human enteric pathogen. We demonstrate that the two major generalist lineages of C. jejuni do not show evidence of recombination with each other in nature, despite having a high degree of host niche overlap and recombining extensively with specialist lineages. However, transformation experiments show that the generalist lineages readily recombine with one another in vitro. This suggests ecological rather than essential barriers to recombination, caused by a cryptic niche structure within the hosts.

Progressive genome‐wide introgression in agricultural Campylobacter coli - Samuel K. Sheppard; Xavier Didelot; Keith A. Jolley; Aaron E. Darling; Ben Pascoe; Guillaume Meric; David J. Kelly; Alison Cody; Frances M. Colles; Norval J. C. Strachan; Iain D. Ogden; Ken Forbes; et al. (Molecular Ecology, 2013)
Hybridization between distantly related organisms can facilitate rapid adaptation to novel environments, but is potentially constrained by epistatic fitness interactions among cell components. The zoonotic pathogens C ampylobacter coli and C . jejuni differ from each other by around 15% at the nucleotide level, corresponding to an average of nearly 40 amino acids per protein‐coding gene. Using whole genome sequencing, we show that a single C. coli lineage, which has successfully colonized an agricultural niche, has been progressively accumulating C. jejuni DNA . Members of this lineage belong to two groups, the ST ‐828 and ST ‐1150 clonal complexes. The ST ‐1150 complex is less frequently isolated and has undergone a substantially greater amount of introgression leading to replacement of up to 23% of the C. coli core genome as well as import of novel DNA . By contrast, the more commonly isolated ST ‐828 complex bacteria have 10–11% introgressed DNA , and C. jejuni and nonagricultural C. coli lineages each have C. coli that colonize agriculture, and consequently cause most human disease, have hybrid origin, but this cross‐species exchange has so far not had a substantial impact on the gene pools of either C. jejuni or nonagricultural C. coli . These findings also indicate remarkable interchangeability of basic cellular machinery after a prolonged period of independent evolution.

Niche segregation and genetic structure of Campylobacter jejuni populations from wild and agricultural host species - SAMUEL K. SHEPPARD; FRANCES M. COLLES; NOEL D. McCARTHY; NORVAL J. C. STRACHAN; IAIN D. OGDEN; KEN J. FORBES; JOHN F. DALLAS; MARTIN C. J. MAIDEN (Molecular Ecology, 2011)
Bacterial populations can display high levels of genetic structuring but the forces that influence this are incompletely understood. Here, by combining modelling approaches with multilocus sequence data for the zoonotic pathogen Campylobacter, we investigated how ecological factors such as niche (host) separation relate to population structure. We analysed seven housekeeping genes from published C. jejuni and C. coli isolate collections from a range of food and wild animal sources as well as abiotic environments. By reconstructing genetic structure and the patterns of ancestry, we quantified C. jejuni host association, inferred ancestral populations, investigated genetic admixture in different hosts and determined the host origin of recombinant C. jejuni alleles found in hybrid C. coli lineages. Phylogenetically distinct C. jejuni lineages were associated with phylogenetically distinct wild birds. However, in the farm environment, phylogenetically distant host animals shared several C. jejuni lineages that could not be segregated according to host origin using these analyses. Furthermore, of the introgressed C. jejuni alleles found in C. coli lineages, 73% were attributed to genotypes associated with food animals. Our results are consistent with an evolutionary scenario where distinct Campylobacter lineages are associated with different host species but the ecological factors that maintain this are different in domestic animals such that phylogenetically distant animals can harbour closely related strains.

Electrocardiogram and cardiovascular changes in thioridazine and chlorpromazine poisoning - E. M. Strachan; C. A. Kelly; D. N. Bateman (European Journal of Clinical Pharmacology, 2004)

U-Pb zircon geochronological evidence for Neoproterozoic events in the Glenfinnan Group (Moine Supergroup): the formation of the Ardgour granite gneiss, north-west Scotland - C. R. L. Friend; P. D. Kinny; G. Rogers; R. A. Strachan; B. A. Paterson (Contributions to Mineralogy and Petrology, 1997)